Ascaris induced acute pancreatitis in paediatric population – a case series - Mahrukh Afreen; Hussain Mustafa; Sajida Qureshi; Javeria Afreen; Ayaz Mansoor; Nimra Shaikh (Journal of the Pakistan Medical Association, 2022)
The most common helminthic parasitic infection inhabiting human intestine is Ascaris lumbricoides (AL). Being the largest of the helminthic family, it infects almost one billion people worldwide, but any information about local population is unavailable especially in children. When patients present with abdominal pain, having ascaris induced pancreatitis never meets the differential diagnosis list even though AL itself is highly prevalent in our part of the world. Infected patients can present with a variety of symptoms depending on the location of parasite. If the biliary tree is inhabited, patients usually present with symptoms of choledocholithiasis or pancreatitis. We report the case series of 3 patients from paediatric age group, having acute pancreatitis secondary to AL. Patients had upper abdominal pain of varying duration. Ultrasound abdomen showed worm inside the Common Bile Duct (CBD) in all 3 patients. Endoscopic retrograde cholangio-pancreatography (ERCP) showed worms coming out of the ampullary orifice. ---Continue